Chapter Catastrophes, the Imaginary and Citizenship The Production of the Other and the Singularity of Experience.of Risk - Mendes, José Manuel (De Gruyter, 2015)
This article reflects on the relationship between the media and the construction of publics, taking these to be based on identities and the processes of creating identities activated in concrete, well-defined contexts. This relationship, which is complex and defined by power dynamics, allows spaces, processes of citizen-ship, and the visibility and invisibility of causes, projects and trajectories to be defined. The central question which serves as the starting point for these reflections is the following: what contribution does the media, with its autonomous operational logic, make towards reflections on citizenship? Who and what does it include and exclude? I intend to approach the specter of theoretical positions on the role played by the media in the production of citizenship from the basis of the polysemic notion of public sphere. Are we demanding too much of the media? Does it real-ly set the agenda for what is relevant in a national and international context?